If A = ⎝ ⎜ ⎜ ⎛ 2 2 1 3 6 7 5 7 6 3 0 0 2 6 1 7 ⎠ ⎟ ⎟ ⎞ , what is the determinant of A − 1 ? Express the answer in the form − b a in lowest terms, and find the sum a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good approach simplifying the determinant calculation.
Problem Loading...
Note Loading...
Set Loading...
∣ A − 1 ∣ = ∣ A ∣ 1 ( p r o p e r t y o f d e t e r m i n a n t i f A i s n o n s i n g u l a r . ) ∣ A ∣ = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 2 2 1 3 6 7 5 7 6 3 0 0 2 6 1 7 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ R 1 → R 1 − 2 R 2 ∣ A ∣ = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ − 2 2 1 3 − 8 7 5 7 0 3 0 0 − 1 0 6 1 7 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ E x p a n d i n g u s i n g 3 r d C o l u m n ∣ A ∣ = − 3 . ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 3 − 8 5 7 − 1 0 1 7 ∣ ∣ ∣ ∣ ∣ ∣ C 2 → C 2 − C 3 ∣ A ∣ = − 3 . ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 3 2 4 0 − 1 0 1 7 ∣ ∣ ∣ ∣ ∣ ∣ C 3 → C 3 − C 1 ∣ A ∣ = − 3 . ∣ ∣ ∣ ∣ ∣ ∣ − 2 1 3 2 4 0 − 8 0 4 ∣ ∣ ∣ ∣ ∣ ∣ R 1 → R 1 − 2 R 3 ∣ A ∣ = − 3 . ∣ ∣ ∣ ∣ ∣ ∣ 4 1 3 2 4 0 0 0 4 ∣ ∣ ∣ ∣ ∣ ∣ e x p a n d i n g u s i n g 3 r d c o l u m n ∣ A ∣ = − 3 . 4 . ∣ ∣ ∣ ∣ 4 1 2 4 ∣ ∣ ∣ ∣ ∣ A ∣ = − 1 2 . ( 1 6 − 2 ) = − 1 2 . 1 4 = − 1 6 8 ∣ A − 1 ∣ = ∣ A ∣ 1 = − 1 6 8 1 = − b a a + b = 1 6 9